Earnings Top-up : staff views - Jill Vincent; Claire Heaver; Simon Roberts; Bruce Stafford (2001)
Background The Department of Social Security introduced Earnings Top-up (ETU) on a pilot basis in October 1996. ETU was an income-related, in-work benefit. It aimed to encourage single people and couples without dependent children to take up work or stay in work of 16 hours a week or more. The pilot ran for three years in eight areas: four received Scheme A ETU at a lower rate; and four matched areas received Scheme B ETU at a higher rate. Four additional matched control areas did not receive ETU. The areas covered four different types of labour market. ETU was operated in the pilot areas through Benefits Agency (BA) and Employment Service (ES) offices, and was centrally processed and administered by the BA in liaison with ES. The design of the evaluation of the pilot integrated three complementary approaches: two quantitative impact studies conducted by the Institute for Employment Research (IER) and the Policy Studies Institute (PSI), and a process evaluation using qualitative methods carried out by the Centre for Research in Social Policy (CRSP). Staff panels of BA and ES staff were held each year in the eight pilot areas and the central administration unit. Reports on earlier meetings were published in an Interim Report (Vincent et al 2000). This is the report on the third round of meetings held early in 1999, it also makes comparisons with the meetings earlier in the pilot.